Foreword. (2019) - Battiston, Simone; Boldrini, Stefano; Castellero, Alberto; Fabrizio, Monica; Fanciulli, Carlo; Fiameni, Stefania; Narducci, Dario
Abstract: The European Conference on Thermoelectricity (ECT) celebrated this year its 15 th meeting. Since its first instance, held in Cardiff in 1987 under the direction of Professor Rowe, the road ECT has walked through has been long and, we may surely say, very successful. Compared to the thirty-five papers of ECT 1987, the attendance to ECT has not only incredibly grown over the years, but has also widely diversified, attracting scientists not only from Europe but also – and in substantial number – from Asia and America, becoming one of the key events for the overall thermoelectric community worldwide. At the same time, research on thermoelectricity has substantially expanded, as well known, moving from 109 papers published in 1987 to more than 2, 300 articles appeared in 2017. No doubt about, thermoelectricity is nowadays a hot research topic, attracting young brilliant minds from all countries and fascinating experienced senior researchers who are entering this field from the most diverse backgrounds